The meeting of East and West : - Northrop, F. S. C. (The Macmillan company, 1947)
The impact of Eastern thought on the culture of the United States and Western Europe is now seen in the spread of Buddhism, meditation, martial arts, yoga, oriental art, and hundreds of other Asian imports. F. S. C. Northrop in this perceptive work was one of the first Americans to grasp the full significance of Eastern culture, its distinctive features, and its potential for influencing the rest of the world. Written during World War II, this classic work correctly anticipated the clash of eastern and western ideologies which has dominated the post-war landscape.